Germicidal lytic bacteriophages a review of isolation and evaluation methods in E. coli - Gonzales Rivasplata, Jose Miguel; Yupanqui Apolinario, Eduardo; Rodriguez Carrillo, Sol Angel; Fernández Tello, Katia (LACCEI, 2024)
Bacteria are developing resistance to medications due to their excessive and inappropriate use, especially affecting the most vulnerable populations around the world, including Peru. In this context, it is necessary to implement alternative methods for the treatment of these multidrug-resistant (MDR) infections. Based on this, the objective of this research is to collect information regarding the isolation, purification and evaluation methods of germicidal lytic bacteriophages in Escherichia coli (E. coli) developed in the last 5 years (2019-2023). To do this, parameters were analyzed such as: matrix of origin, identification of culture media, sequence of procedures and technical variables that are collected, compared and analyzed, taking into account the approach of different researchers in the world for the study of bacteriophages that interact. with the bacteria E. coli. For this, the search for information was carried out in the electronic databases of Sciencedirect, Pubmed and Scopus, excluding articles as explained in the methodology and finally selecting twenty-four relevant articles which were classified, ordered, analyzed and compared for evaluation. full text. In conclusion, a general sequence of steps was established for the isolation, purification and evaluation of specific bacteriophages in E. coli strains, taking into account the main physicochemical and microbiological tests used by different researchers around the world in this field. The potential application in various settings, such as the food industry, agriculture and public health, underlines the relevance of this research in the search for effective and safe alternatives to chemical antimicrobials to reduce microbial contamination by E. coli strains.